A Review of Reversible Medical Image Watermarking Scheme with Tamper Localization and Recovery Capability - Khor, Hui Liang; Liew, Siau-Chuin; Jasni, Mohamad Zain (IEEE, 2014)
With the advancement of technology in communication network, it facilitated digital medical images transmitted to healthcare professional via internal network or public network (e.g. Internet). Consequently, digital medical image security has become an important issue when images and their pertinent patient information are exposed to the threats, such as tampering of images to include false data which may lead to wrong diagnosis and treatment. Medical image distortion is not to be tolerated for diagnosis purposes, thus a reversible watermarking is introduced. This paper reviews the works that have done on the reversible watermarking scheme with tamper localization and recovery capability.